1991
DOI: 10.1002/yea.320070412
|View full text |Cite
|
Sign up to set email alerts
|

III. Yeast sequencing reports. Sequence of the CDC10 region at chromosome III of Saccharomyces cerevisiae

Abstract: A 4.74 kb DNA fragment from the right arm of chromosome III of Saccharomyces cerevisiae, adjacent to the centromere region was sequenced. Four open reading frames with an ATG initiation codon and larger than 200 bp were found in this fragment. The largest open reading frame of 966 bp was identified as the CDC10 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Of the 1,305 bp sequenced, one deviation was found between the wildtype Y574 sequence and that reported by Steensma and van der Aart (1991). We assume that this difference represents a PCR/cioning error in our sequence, because the sequence from the other two cdclO-lO strains matched the published sequence at this position.…”
Section: Sequencing the Cdclo-lo Mutationmentioning
confidence: 69%
“…Of the 1,305 bp sequenced, one deviation was found between the wildtype Y574 sequence and that reported by Steensma and van der Aart (1991). We assume that this difference represents a PCR/cioning error in our sequence, because the sequence from the other two cdclO-lO strains matched the published sequence at this position.…”
Section: Sequencing the Cdclo-lo Mutationmentioning
confidence: 69%
“…The HmdIII fragments from pVC2a, pVC2b and pVC2c were cloned into pUC19 to facilitate sequencing from universal and reverse primers, and both strands of each clone were sequenced twice. Analysis of these sequences revealed only one point mutation with respect to the published sequence of CDC10 (Steensma & Van der Aart, 1991). Consistent with the mechanism of action of the mutagen used (Cid et al, 1994), there was a G to A change, which implies a substitution of the glycine in position 179 with aspartate in the encoded protein.…”
Section: Resultsmentioning
confidence: 94%
“…Like all of the known septins, Spr3p contains a putative nucleotide-binding domain; however, the function of this domain, and whether it is indeed involved in nucleotide binding, remain to be determined. Like all of the known septins except Cdcl0p (Steensma and van der Aart, 1991;Haarer, B. K., S. R. Ketcham, and J. R. Pringle, unpublished results), C. albicans Cdcl0p (Di-Domenico et al, 1994), and S. pornbe Spn2p (AI-Awar, O., T. Pugh, and J. R. Pringle, unpublished results), Spr3p contains a region near its COOH terminus that is strongly predicted to form a coiled coil. This region in Spr3p is un-usual in consisting of two predicted coiled-coil domains separated by ~50 amino acids, rather than the single, continuous domain found in the other known septins.…”
Section: Discussionmentioning
confidence: 99%
“…In immunofluorescence and immunoelectron microscopy experiments, antibodies specific for the products of these four genes decorate the neck region of wild-type cells in the pattern expected if these proteins are constituents of the neck filaments; moreover, upon shift of any of the four mutants to restrictive temperature, immunofluorescence staining of the necks with each of the four specific antibodies disappears at the same rate as do the filaments as judged by electron microscopy (Haarer and Pringle, 1987;Kim et al, 1991;Ford and Pringle, 1991;Kim, H., B. Haarer, and J. R. Pringle, unpublished results;Mulholland, J., D. Preuss, and D. Botstein, personal communication). Sequencing revealed that Cdc3p, Cdcl0p, Cdcl lp, and Cdcl2p constitute a family of related proteins (25-37% identical in amino acid sequence) (Steensma and van der Aart, 1991;Haarer, B. K., S. H. Lillie, S. K. Ford, S. R. Ketcham, and J. R. Pringle, unpublished results;Longtine et al, 1996). All four proteins contain sequences conserved among nucleotide-binding proteins, a feature shared with the related proteins from other organisms.…”
mentioning
confidence: 99%